My book of frogs and toads - Valério, Geraldo, 1970- (Big books for little naturalists, 2025)
"Leap into this stunning exploration of frogs and toads from around the world! A companion to My Book of Butterflies and My Book of Birds. When Geraldo Valério was growing up in Brazil, he learned that the tiny creatures he saw swimming in a puddle by the river weren't fish, but tadpoles that would grow and change into entirely different creatures ... and his fascination with frogs and toads began! In this gorgeous album, Geraldo presents his favorite frog and toad species from around the world. Dazzling paint and paper collage illustrations introduce us to a wide range of creatures: meet the frog who can grow to the size of a small housecat, and the toad who spends most of its life in an underground burrow. Learn fascinating frog and toad facts about what they like to eat, how they grow and reproduce and why one particular toad smells like garlic! Colorful endpapers, showing the frogs and toads as eggs and tadpoles, complete this beautiful book for budding young naturalists. Includes an introduction, world map, a diagram of a frog and toad's life cycle, a chart explaining the differences between frogs and toads, as well as a glossary, index and suggestions for further reading."--